(untitled) (Colombia Medica, 1986)
Members of the genus Rhodnius are important vectors of Chaga’s disease and of Trypanosoma rangeli, the second trypanosome of man in the Americas. Some general considerations on Colombian triatomines are made, and a key to all of the known species of Rhodnius is given.